2020
DOI: 10.1093/mnrasl/slaa016
|View full text |Cite
|
Sign up to set email alerts
|

The impact of isomers on a kilonova associated with neutron star mergers

Abstract: We investigate the significance of isomers on a kilonova associated with neutron star mergers (NSMs) for the first time. We calculate the evolution of abundances and energy generation rates (ǫ nuc ) of ejecta from NSMs, taking into account β − decay through isomers. We find that for ejecta with electron fraction (Y e ) of 0.2 − 0.3,ǫ nuc is appreciably changed from those without isomers, due to the large change in timing of β − decay through the isomeric states of 123,125,127 Sn and 128 Sb. In particular, the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 22 publications
1
15
0
Order By: Relevance
“…Despite being known in the contexts discussed above, isomers have only recently been included in larger networks, such as those that describe the r process that is believed to occur in explosive environments [46]. Fujimoto and Hashimoto [47] included the direct population of nuclear isomers in the r process by replacing GS properties with isomer properties. In their study, several hand-picked isomers in the second r-process peak were shown to impact the radioactive heating of a kilonova.…”
Section: Introductionmentioning
confidence: 99%
“…Despite being known in the contexts discussed above, isomers have only recently been included in larger networks, such as those that describe the r process that is believed to occur in explosive environments [46]. Fujimoto and Hashimoto [47] included the direct population of nuclear isomers in the r process by replacing GS properties with isomer properties. In their study, several hand-picked isomers in the second r-process peak were shown to impact the radioactive heating of a kilonova.…”
Section: Introductionmentioning
confidence: 99%
“…Both situations provide a clean tag of the reaction channel involving a 8 Be ejectile. The 12 C ejectiles can be partially separated from the 13 C target nuclei although it is less clean than the 9 Be case. The Doppler correction was made according to the ring of BareBall where the emergent α particles, or 12 C nucleus, were detected, which relates directly to the angle and nominal β =v/c of the recoiling 131 Sn.…”
Section: Methodsmentioning
confidence: 99%
“…However, this tendency is moderated by the weak binding of 9 Be (S n = 1.66 MeV). In contrast, ( 13 C, 12 C) preferentially populates states with j > = + 1/2, owing to the dominantly p 1/2 nature of the last neutron in 13 C. The relative cross sections for these states were measured using the γ-ray intensities (shown in Figure 4) normalized to the number of elastically scattered beam particles detected in the innermost ring of BareBall. The figure does not show the optimal Doppler correction for all peaks, as one value of β had to be selected for all the lines, resulting in some peaks being centered away from their true energy, and counts being dispersed across more channels.…”
Section: Spin-parity Assignmentsmentioning
confidence: 99%
See 2 more Smart Citations